2019
DOI: 10.1177/0954407019827131
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective design optimization of a high efficiency and low noise blower unit of a car air-conditioner

Abstract: Car air-conditioners consist of a blower unit and a heater unit. A blower unit sends wind to a heater unit, and a heater unit adjusts the temperature inside the vehicle. Blower units of car air-conditioners are required to be smaller, lighter, noiseless, and power-saving. However, it is difficult and expensive to predict the noise directly by computational fluid dynamics simulation. Hereupon, this study employs an indirect noise prediction method based on a noise prediction theory to evaluate noise for blower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Masaru Kamada et al [11] focused their attention on reducing the noise that the car air-conditioner blower is producing and at the same time, having an impeller with a higher efficiency. The method they used is radically basic, not relaying on numerical simulations for sound testing and results, using a measurement facility for acknowledge the sound pressure level (SPL).…”
Section: Introductionmentioning
confidence: 99%
“…Masaru Kamada et al [11] focused their attention on reducing the noise that the car air-conditioner blower is producing and at the same time, having an impeller with a higher efficiency. The method they used is radically basic, not relaying on numerical simulations for sound testing and results, using a measurement facility for acknowledge the sound pressure level (SPL).…”
Section: Introductionmentioning
confidence: 99%
“…Iwamoto et al (2015) suggested that an HVAC heater unit with straight flow channels is effective to enhance heat performance, pressure loss reduction, and noise reduction at the same time. Moreover, Kamada et al (2019) optimized the shapes of multi-blade fan and scroll in an HVAC blower unit using a CFD solver based on the Reynolds-averaged Navier-Stokes (RANS) equations and a genetic algorithm. The optimized design outperformed the baseline design in terms of both total pressure efficiency and noise level.…”
Section: Introductionmentioning
confidence: 99%
“…Kamada et al 7 employed an indirect noise prediction method to theoretically evaluate noise for blower units. This method was validated through a comparison with actual sound pressure level measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that a mixed flow fan consisting of seven evenly spaced blades with backward swept shape produced the low-noise fan design at the fan operating point. Kamada et al 7 employed an indirect noise prediction method to theoretically evaluate noise for blower units. This method was validated through a comparison with actual sound pressure level measurements.…”
Section: Introductionmentioning
confidence: 99%